Biodiversity in wetland+ system: a passive solution for HCH dump effluents - Amirbekov, Aday; Strojsova, Martina; Nemecek, Jan; Riha, Jakub; Hrabak, Pavel; Arias, Carlos; Sevcu, Alena; Černík, Miroslav (Water science and technology, 2023)
The hexachlorocyclohexane isomers (HCH) are long-banned pesticides. Even though their use has been prohibited for decades, their presence in the environment is still reported worldwide. Wetland + is a registered trademark of the remedial treatment technology consisting of an aerobic sedimentary tank, a permeable reactive barrier, a biosorption system, and an aerobic wetland. This proven method combines a reductive treatment known from PRBs with the natural wetland self-cleaning processes. The average efficiency of the system is 96.8% for chlorobenzenes (ClB) and 81.7% for HCH, during the first 12 months of the system operation. The presence of the genes encoding enzymes involved in the degradation of the HCH compounds indicates that the removal of HCH and ClB occurs not only by chemical removal but also through aerobic and anaerobic combining biodegradation. Changes in abundance and the composition of the diatom community were found to be suitable indicators of the water quality and of the impact of the Wetland + operation on the water ecosystem. The system's annual operation exhibited a markedly higher number of diatom species in the closing profiles of the Ostrovský Creek, the Wetland + effluent recipient.
Keywords: hexachlorcyklohexan; Wetlands; biodegradace; Biodegradation, Environmental; Biodiversity; mokřady; ekosystém; Ecosystem; biodiverzita; Hexachlorocyclohexane